Thermal and Structural Optimization of Parabolic Trough Systems for Enhanced Energy Conversion Efficiency - Muhammad Sajjad; Shahryar Shafique Qureshi; Samrat Ray; Ambe Harrison; Saad F. Al-Gahtani; Zakaria M. S. Elbarbary (IEEE Access)
This study investigates the optimization of solar thermal energy systems through MATLAB simulations, focusing on critical parameters such as concentration ratio, optical efficiency, heat transfer, energy storage, and receiver design. The aim is to enhance the overall performance of these systems by analyzing key factors such as source temperature effects on absorbance, angular errors in optical efficiency, and the impact of heat transfer fluids and material properties on system efficiency. The methodology includes modeling energy storage with phase change effects, assessing focal efficiency in parabolic concentrators, and comparing various absorber and receiver designs. Additionally, the study evaluates system performance for different concentration ratios and thermal efficiencies. Key results highlight a significant increase in absorbance (57.7%) with rising temperatures and a notable decrease in optical efficiency (65%) with increasing angular errors. Furthermore, energy storage demonstrates a 17,000 kJ increase between 500K and 600K, showing potential for enhanced energy retention at higher temperatures. The findings provide valuable insights into optimizing system components, contributing to the design of more efficient solar thermal systems with improved energy collection and storage capabilities. These results underscore the importance of precise design adjustments for maximizing system efficiency in practical applications.